ANALYSIS OF STABILITY OF SLOPE AND EMBANKMENT AT LANDFILL USING THE 2012 GEOSTUDIO SLOPE/W PROGRAM - Eka Priska Kombong; Harni Eirene Tarru; Marchelina Rante (Journal Dynamic Saint, 2022)
The increase in waste production every year continues to increase along with the increasing rate of population growth in Indonesia so that the construction of landfills is something that needs special attention from the government. The disaster that has occurred related to landfills is the landslide disaster at the Leuwijgajah landfill, West Java, which claimed up to 156 people. Therefore, landfill slope stability analysis is a very important parameter in determining the feasibility of a landfill construction. This study aims to analyze the stability of slopes and embankments at the Banjar Bakula Regional Waste Landfill, South Kalimantan using Slope/W. The analysis was carried out using two models, namely using the initial planning design and analyzing based on the PUPR Ministerial Regulation 03/PRT/M/2013 concerning the Implementation of Waste Infrastructure and Facilities in the Handling of Household Waste and Types of Household Waste. The results of this study indicate that the slopes of the landfill and embankments at the Banjar Bakula Regional Landfill are declared safe with a safety factor value above 1.5, namely 1.558 – 1.651 for modeling with the initial planning design and 2.052 – 2.068 for modeling based on the PUPR Ministerial Regulation 03/PRT/M/2013, and 1.943 – 2.168 for the safety factor from embankment.